2018
DOI: 10.1117/1.jpe.8.032102
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-dependent investigation of carbazole benzonitrile derivatives: does the LE3−CT1 energy gap facilitate thermally activated delayed fluorescence?

Abstract: , "Solvent-dependent investigation of carbazole benzonitrile derivatives: does the 3 LE − 1 CT energy gap facilitate thermally activated delayed fluorescence?," J. Photon. Energy 8(3), 032102 (2018), doi: 10.1117/1.JPE.8.032102. Abstract. The photophysical properties of six types of carbazole benzonitrile (CzBN) derivatives are investigated in different solvents to examine the thermally activated delayed fluorescence (TADF) activation via reducing the energy gap between the singlet charge-transfer and triplet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 34 publications
(48 reference statements)
7
27
0
Order By: Relevance
“…While Hosokai et al . ( 24 ) already reported that the T 1 state of 5CzBN has CT character, we also confirmed the solvatochromism of the phosphorescence spectra of 5CzBN (fig. S2), indicating that the T 1 state of 5CzBN has more CT character than LE character despite the vibronic phosphorescence spectra.…”
Section: Resultssupporting
confidence: 89%
“…While Hosokai et al . ( 24 ) already reported that the T 1 state of 5CzBN has CT character, we also confirmed the solvatochromism of the phosphorescence spectra of 5CzBN (fig. S2), indicating that the T 1 state of 5CzBN has more CT character than LE character despite the vibronic phosphorescence spectra.…”
Section: Resultssupporting
confidence: 89%
“…Secondly, we point out that our measurements are made using chloroform as a solvent rather than toluene (commonly used for 4CzIPN) because the TADF was more intense for our molecules in chloroform. This result is consistent with literature findings for 4CzIPN and various carbazole benzonitrile derivatives where the reverse intersystem crossing rate is increased in solvents more polar than toluene (Ishimatsu et al, 2013;Nobuyasu et al, 2016;Hosokai et al, 2018). The decrease in the TADF emission for 4CzIPN in more polar solvents than toluene is attributed to increased nonradiative rates (Ishimatsu et al, 2013).…”
Section: Uv-vis Absorption and Photoluminescence Spectroscopysupporting
confidence: 92%
“…High-throughput screening approaches have been proposed [29][30][31] to find new emitters with an effective tradeoff between small Δ and fast radiative decay. Further experimental 15,[32][33][34] studies have shown that for many TADF molecules the lowest triplet state is in fact a local excitation (LE), which indicated that the understanding of the TADF mechanism is incomplete and known design strategies are not optimal. Since then, a number of theoretical works have analyzed the mixed CT/LE nature of the excited states [35][36][37][38][39][40] , importance of vibronic effects [41][42][43][44][45] , and influence of the interactions with the environment [46][47][48][49] , including the importance of static and dynamic disorder 50,51 .…”
Section: Introductionmentioning
confidence: 99%